2008
DOI: 10.5194/acp-8-7493-2008
|View full text |Cite
|
Sign up to set email alerts
|

Cloud phase identification of Arctic boundary-layer clouds from airborne spectral reflection measurements: test of three approaches

Abstract: Abstract. Arctic boundary-layer clouds were investigated with remote sensing and in situ instruments during the Arctic Study of Tropospheric Aerosol, Clouds and Radiation (ASTAR) campaign in March and April 2007. The clouds formed in a cold air outbreak over the open Greenland Sea. Beside the predominant mixed-phase clouds pure liquid water and ice clouds were observed. Utilizing measurements of solar radiation reflected by the clouds three methods to retrieve the thermodynamic phase of the cloud are introduce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 46 publications
2
80
0
Order By: Relevance
“…Ten HALO research flights from Barbados are envisioned, each with a duration of 9 h bracketing two 4-h flights of the ATR-42 (with a refuelling in between). (Wirth et al 2009) SMART Up-and downward-looking spectral (300-2200 nm) radiance and irradiance measurements (Wendisch et al 2001;Ehrlich et al 2008) SpecMACS Downward-looking hyper-spectral (400-2500 nm) line imager Thermal imager Downward-looking (10.8 and 12 lm) two channel line imager (in development) Dropsondes AVAPs system with four-channel receiver supporting Vaisala RD94 Sondes (ten channel receiver in development)…”
Section: Aircraft Measurementsmentioning
confidence: 99%
“…Ten HALO research flights from Barbados are envisioned, each with a duration of 9 h bracketing two 4-h flights of the ATR-42 (with a refuelling in between). (Wirth et al 2009) SMART Up-and downward-looking spectral (300-2200 nm) radiance and irradiance measurements (Wendisch et al 2001;Ehrlich et al 2008) SpecMACS Downward-looking hyper-spectral (400-2500 nm) line imager Thermal imager Downward-looking (10.8 and 12 lm) two channel line imager (in development) Dropsondes AVAPs system with four-channel receiver supporting Vaisala RD94 Sondes (ten channel receiver in development)…”
Section: Aircraft Measurementsmentioning
confidence: 99%
“…Cloud thermodynamic phase affects radiative forcing by modulating absorption of incoming solar radiation, particle evolution, and lifetime (Ehrlich et al, 2008;. Previous satellite observational studies have shown that clouds are shifting poleward in the northern and southern hemispheric extratropical storm tracks (Bender et al, 2012;Marvel et al, 2015;Norris et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…During these missions, a suite of different active and passive remote sensing instruments was operated on board HALO, including passive solar radiance measurements by SMART Ehrlich et al, 2008) and the mini-DOAS (Hüneke, 2016). While SMART measured radiometrically calibrated radiance I N S in the nadir direction, the mini-DOAS instrument simultaneously measures in the nadir and varying sideward viewing directions in UV/VIS/IR wavelength ranges.…”
Section: Airborne Measurementsmentioning
confidence: 99%
“…The system is extensively described in Wendisch et al (2001) and Ehrlich et al (2008). In this paper the focus is on I N S measurements which are available for the four HALO missions introduced above.…”
Section: The Smart Instrumentmentioning
confidence: 99%